Chemical and Antimicrobial Examination of the Fixed Oil from the Seeds of Adenanthera pavonina Linn. - Chourasia, O.P.; Rao, J.T. (Asian Journal of Chemistry, 2016)
The seeds of Adenanthera pavonina Linn. have been found to contain fixed oil (7.5%), crude protein (4.5%), reducing sugars (3.16%) as glucose and unsaponifiable matter (1.36%). The deep-brownish yellow fixed oil has been found to be the glyceride of palmitic (19.06%), stearic (3.66%), arachidic (4.53%) and lignoceric (11.05%) as saturated (38.24%) fatty acids and oleic (24.12%) and linoleic (37.04) as unsaturated (61.16%) fatty acids. The unsaponifiable matter consists of stigmasterol. The oil has shown feeble activity (comparable to achromycin/streptomycin) against Bacillus anthracis, Salmonella paratyphi and B. mycoides. It is totally ineffective against the rest of the test gram positive and gram negative plant and/or animal pathogenic bacteria.